A Case of Premature Ovarian Failure in a 33-Year-Old Woman. (29th January 2013) - Colao, Emma; Granata, Teresa; Vismara, Marco F. M.; Bombardiere, Francesco; Nocera, Donatella; Luciano, Elisa; Perrotti, Nicola; Malatesta, Paola
Abstract : Objective . To assess aetiology of a POF in a 33-year-old woman and, if possible, plan a cure. Design . Case report. Setting . medical genetics diagnostic unit in a university hospital. Patient . A 33-year-old woman with premature ovarian failure (POF). Intervention(s) . Genetic counseling, karyotyping, FISH study. Result(s) . Turner-like diagnosis. Conclusion(s) . Most cases of POF remain idiopathic. Turner syndrome can occur in very different phenotypes; cytogenetic and molecular profiling can provide a definitive diagnosis in cases with nonclassical phenotype.